2021
DOI: 10.3390/nano11112963
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of Graphene-Based Materials: Impact of the Surface Chemistry, Surface Specific Area and Lateral Size on Their In Vitro Toxicity

Abstract: Predictive toxicity and structure–activity relationships (SARs) are raising interest since the number of nanomaterials has become unmanageable to assess their toxicity with a classical case-by-case approach. Graphene-based materials (GBMs) are among the most promising nanomaterials of this decade and their application might lead to several innovations. However, their toxicity impact needs to be thoroughly assessed. In this regard, we conducted a study on 22 GBMs to investigate their potential SARs by performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In this regard, we can probably rule out a direct clastogenicity mechanism. Some GBMs appear to have a high genotoxic impact even at quite low doses, this is not completely surprising as some of these samples also show a very high impact for other in vitro studies performed on RAW 264.7 (Achawi et al 2021a) and on an acellular FRAS assay (Achawi et al 2021b).…”
Section: In Vitro Studiesmentioning
confidence: 82%
See 1 more Smart Citation
“…In this regard, we can probably rule out a direct clastogenicity mechanism. Some GBMs appear to have a high genotoxic impact even at quite low doses, this is not completely surprising as some of these samples also show a very high impact for other in vitro studies performed on RAW 264.7 (Achawi et al 2021a) and on an acellular FRAS assay (Achawi et al 2021b).…”
Section: In Vitro Studiesmentioning
confidence: 82%
“…Cells were then exposed to GBMs with exposure doses from 8 to 75 µg/cm² for 24 hours. ROS production was measured through OxiSelect™ Intracellular ROS Assay Kit (STA-342) as previously reported (Achawi et al 2021a).…”
Section: Dcfh-da Assaymentioning
confidence: 99%
“…The toxicology of carbon nanomaterials was studied for carbon nanotubes [1][2][3][4][5][6][7][8][9][10][11][12][13][14], graphene [15][16][17][18][19][20][21][22][23][24][25][26][27][28], fullerenes [29][30][31][32][33], and dots [34][35][36][37][38]. Most of the work deals with microorganisms, animals, and humans.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity induced by graphene materials was tested in various species, such as prokaryotes, bacteria, viruses, plants, invertebrates and mammals, including human and animal cells [ 5 , 6 , 7 , 8 , 9 , 10 ]. Several studies suggest that the size of the material will determine how it interacts with cells [ 11 , 12 , 13 ]. A previous work carried out with diverse cell lines has shown that GO with different side-chain dimensions has been able to cross the cell membrane [ 2 ].…”
Section: Introductionmentioning
confidence: 99%